Pemanfaatan Getah Biduri (Calotropis gigantea) DAN BUAH LERAK (Sapindus rarak) SEBAGAI PESTISIDA NABATI PEMBASMI KEONG MAS (Pomacea canaliculata L.) - Mayasari, Santika Linda, Dr. H. Sofyan Anif, M.Si (2016)
The use of botanical pesticides in order to control the Plant Pest organism (PPO) is the last alternative, the impact should a be minimal as possible. Selected botanical pesticide from Biduri sap (Calotropis gigantea) and Lerak Fruit (Sapindus rarak). The purpose of this study to know greater the concentration of Biduri sap and Lerak Fruit most optimal killing Golden Apple Snail in a shorter time, and to identify changes in morphology, behavior, and survival of Golden Apple Snail after given botanical pesticide with different concentration.The research was conducted between February to April 2016. This study used Completed Random Design (CRD) and repeat 2 times. Data collection techniques through the experimental method, observation, literature review, documentation. L3.B3 treatment that kills Golden Apple Snail fastest at 12 hours after being given a pesticide plant L3 0,15 gr/ml and B3 0,06 ml/ml. Treatment L0.B1 and L0.B2 kills longest at 12 o'clock to 6, L0 0 gr/ml, B1 0,01 ml/ml, B2 0,03 ml/ml. Analysis through One Way Anova test get p =0,000,this means are differences in the time it takes for dead Golden Apple Snail among all treatment. Spearman rank correlation test showed the value of -0,647, so the higher concentrations of botanical pesticide, the lower time required Golden Apple Snail for live. The results of this study indicate sap biduri and lerak fruit contain subtances that are toxic to snails.This is ecidenced by signs of Golden Apple Snail such as: pulled herself into a shell, operculum is closed, pull out the bubbles and mucus, not moving, followed signs death: the body protrudes out, open operculum, the body is brown to orange. Keyword: Biduri, Botanical Pesticide, Golden Apple Snails, Lerak